Energy savings in SWRO desalination via PRO hybridization: a parametric study - Alghamdi, Ahmed S.; Mahmoud, Amr Mohamed; Ahmed, Sultan (Frontiers in Water, 2025)
This study investigates the potential for energy reduction in a full-scale Seawater Reverse Osmosis (SWRO) desalination plant through hybrid integration with Pressure Retarded Osmosis (PRO). A pilot test using a 60 m2 PRO membrane kit helped determine key operating parameters, including draw solution (DS) pressure and resulting dilution fluxes. Subsequently, a full-scale analysis was conducted with 650 m2 of PRO membrane area. The integration demonstrated up to 12.56% reduction in specific energy consumption under optimized conditions. Energy savings were found to correlate positively with lower feed pressures, higher brine availability, and optimal dilution rates, while being negatively impacted by pressure losses and high DS-to-FS flow ratios. The study confirms the viability of PRO-SWRO hybridization as a method for enhancing desalination energy efficiency, and highlights areas for further optimization in membrane design and hydraulic configuration.